Neurological disorders are associated with bullous pemphigoid. (27th February 2019) - Papakonstantinou, E.; Limberg, M.M.; Gehring, M.; Kotnik, N.; Kapp, A.; Gibbs, B.F.; Raap, U.
Abstract: Background: Bullous pemphigoid (BP) is the most common subepidermal autoimmune blistering disease with an increased incidence particularly among the elderly. Several studies have recently reported an association between BP and neurological disorders. Objective: To evaluate the association between BP and neurological disorders in a single centre in Germany. Methods: We retrospectively assessed 183 patients with BP (diagnosed between 2011 and 2015) and 348 age‐ and sex‐matched controls for neurological disorders. The latter were confirmed either by a neurologist or psychiatrist. Results: Overall, there was a highly statistically significant association between BP and neurological disorders ( P < 0.0001). These included dementia ( P < 0.0001), Parkinson`s disease ( P = 0.0434), stroke ( P = 0.0015) and other neurological disorders but not Alzheimer's diseases, which was more common among patients in the control group. Conclusion: Our cohort of bullous pemphigoid and neurological disorders demonstrates a significant association between bullous pemphigoid and neurological disorders, including dementia, Parkinson's disease and stroke. These observations support the need for future studies in order to elucidate the immunological mechanisms responsible for these comorbidities.